Intelligent Sensors and Monitoring System for Low-Cost Phototherapy Light for Jaundice Treatment. - Cabacungan, Paul M (Archīum Ateneo, 2019)
A prototype of a low-cost phototherapy light system (LPLS) was deployed by the Ateneo Innovation Center (AIC) at a public hospital in Metro Manila, Philippines. It underwent clinical investigation for two years under the supervision of licensed physicians in a public tertiary hospital. This paper presents the process of upgrading the LPLS in order to enhance capabilities and improve efficiency yet remain affordable. The following features were added: (1) a visual and auditory monitoring system in order to remotely oversee the infant from the nurse station; (2) an automation system that stores data about the device's light intensity and bulb temperature and records ambient humidity; (3) an alarm system that activates the warning lights if sensor readings are in critical level and if the bulbs need to be replaced; and (4) a time setting to manually set the time of operation and automatically turn-off the device as programmed The upgrades increased the system's cost but it remained cheaper than the ones commercially available. For deployment in remote or off-grid hospitals, the system was equipped with a solar-powering provision.